Colombian Ocular Infectious Epidemiology Study (COIES): Ocular Toxoplasmosis Incidence and Sociodemographic Characterization, 2015-2019 - Cifuentes-González, Carlos; Zapata-Bravo, Estefanía; Sierra-Cote, María Camila; Boada-Robayo, Laura; Vargas-Largo, Ángela Paola; Reyes-Guanes, Juliana; de-la-Torre, Alejandra (International journal of infectious diseases, 2022)
This study aims to describe the incidence of ocular involvement in patients with toxoplasmosis and describe the sociodemographic characteristics by age, sex, and region in Colombia, based on the National Health Registry of data between January 1, 2015, and December 31, 2019. We conducted a cross-sectional study using the Integrated Social Protection Information System database from the Colombian Ministry of Health, the unique official database in the country. We used the International Classification of Diseases for all codes of toxoplasmosis with a specific filter for ocular toxoplasmosis (OT) from 2015 to 2019 to estimate the incidence and the demographic status of the disease in Colombia. During the 5 years of study, the crude unadjusted incidence of OT was 42.02 (Confidence Interval 30.29-56.19) cases in 1,000 patients with toxoplasmosis per year, showing a significant increase of incidence when comparing the year 2019 to the year 2015. There was a predominance of female patients (58% of the cases). The distribution by age shows an increase in cases of the disease in subjects aged 15 to 49 years (65.2%). The geographic analysis showed a higher proportion of cases in the Andean region, followed by the Pacific and the Atlantic regions. This is the first study that determines the epidemiological characteristics of OT based on a National Health database in Colombia, showing a public health problem and evidencing the neediness of solidifying preventive and screening strategies in the Colombian population.